Comparative Quality Evaluation of Physicochemical, Technological, and Protein Profiling of Wheat, Rye, and Barley Cereals - Rani, Monika; Singh, Gagandeep; Siddiqi, Raashid Ahmad; Gill, Balmeet Singh; Sogi, Dalbir Singh; Bhat, Mohd Akbar (Frontiers in Nutrition, 2021)
Agronomically important cereal crops wheat, Barley and Rye of Triticeace tribe under the genus Triticum were studied with special focus on their physical, proximal and technological characteristics which are linked to their end product utilization. The physiochemical parameters showed variability among the three cereal grains. Lactic acid-Solvent Retention Capacity (SRC) was found higher in wheat (95.86–111.92 %) as compared to rye (53.78–67.97 %) and barley (50.24–67.12 %) cultivars, indicating higher gluten strength. Sucrose-SRC and sodium carbonate-SRC were higher in rye as compared to wheat and barley flours. The essential amino acid proportion in barley and rye cultivars was higher as compared to wheat cultivars. Barley and rye flours exhibited higher biological value (BV) owing to their higher lysine content. SDS-PAGEof wheat cultivars showed a high degree of polymorphism in the low molecular range of 27.03–45.24 kDa as compared to barley and rye cultivars. High molecular weight (HMW) proteins varied from 68.38–119.66 kDa (4–5 subunits) in wheat, 82.33–117.78 kDa (4 subunits) in rye and 73.08–108.57 kDa (2–4 subunits) in barley. The comparative evaluation of barley and rye with wheat cultivars would help in the development of healthy food products.